2021
DOI: 10.1111/aogs.14058
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different endometrial preparations on women with polycystic ovary syndrome undergoing initial frozen embryo transfer: A historical cohort analysis

Abstract: Introduction:Frozen embryo transfer is associated with a higher rate of live birth and a lower risk for ovarian hyperstimulation syndrome in women with polycystic ovary syndrome (PCOS) compared with fresh embryo transfer. The aim of this study is to assess the optimal endometrial preparation protocol for women with PCOS undergoing frozen embryo transfer. Material and methods:We conducted a historical cohort analysis of 1720 women with PCOS who underwent the "freeze-all" strategy between August 2014 and August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…In detail, that LBR with HRT accompanied by the poorest endometrial thickness, is lower than OS with low doses of human menopausal gonadotropin. 15 Peigne et al verified the same perspective, despite a similar CPR (24.4% vs 20.8%), LBR (17.1% vs 9.8%) was significantly higher with mild OS than with HRT preparation, even after adjusting for potential bias, such as patient age at freezing, PCOS, and so on. 24 In Jouan et al’s retrospective study, he demonstrated the superiority of clomiphene citrate cycles over HRC not only in OPR but also CPR.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…In detail, that LBR with HRT accompanied by the poorest endometrial thickness, is lower than OS with low doses of human menopausal gonadotropin. 15 Peigne et al verified the same perspective, despite a similar CPR (24.4% vs 20.8%), LBR (17.1% vs 9.8%) was significantly higher with mild OS than with HRT preparation, even after adjusting for potential bias, such as patient age at freezing, PCOS, and so on. 24 In Jouan et al’s retrospective study, he demonstrated the superiority of clomiphene citrate cycles over HRC not only in OPR but also CPR.…”
Section: Discussionmentioning
confidence: 79%
“… 39 Excessive estrogen may have adverse effects on the pregnancy outcome of anovulatory women, resulting in lower LBR. 15 , 40 Embryo implantation is not only related to the serum progesterone level but also the inner membrane. 25 When the progesterone value exceeded 20 ng/dl which is associated, overall pregnancy rate and live birth rate would become lower, spontaneous abortion rate and biochemical pregnancy rate become higher.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations